2011
DOI: 10.1017/s1368980011002710
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of street foods to the dietary needs of street food vendors in Kampala, Jinja and Masaka districts, Uganda

Abstract: Objectives: To assess the contribution of street foods to the energy and nutrient needs of street food vendors. Design: A cross-sectional descriptive study was conducted. Food intake for the street food vendors was measured using the 24 h recall method and a semiquantitative FFQ with emphasis on the source of all foods consumed. Setting: Kampala, Jinja and Masaka districts, Uganda. Subjects: The study included 225 street food vendors trading in prepared cooked foods.Results: The majority of vendors (87?6 %) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 11 publications
3
39
0
1
Order By: Relevance
“…Furthermore, a systematic review on nutritional contribution of street food in developing countries reported a high contribution of street food to total intakes of fat, trans fatty acids and sugar . Considering that street foods contribute to a significant proportion of the daily energy intakes of people in developing countries , its low nutritional quality raises concerns, because it potentially contributes to obesity, diabetes, hypertension, dyslipidaemia and other diet‐related noncommunicable diseases , in countries that are under epidemiological transition. However, street food offer is extremely variable across countries and cultures, with different ingredients and methods of preparation and cooking, thus differing in nutritional value .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a systematic review on nutritional contribution of street food in developing countries reported a high contribution of street food to total intakes of fat, trans fatty acids and sugar . Considering that street foods contribute to a significant proportion of the daily energy intakes of people in developing countries , its low nutritional quality raises concerns, because it potentially contributes to obesity, diabetes, hypertension, dyslipidaemia and other diet‐related noncommunicable diseases , in countries that are under epidemiological transition. However, street food offer is extremely variable across countries and cultures, with different ingredients and methods of preparation and cooking, thus differing in nutritional value .…”
Section: Discussionmentioning
confidence: 99%
“…According to the FAO, street‐vended foods and beverages can have a significant positive nutritional impact, provided that consumers are able to make appropriate choices . The nutritional value of street food, however, greatly depends on the ingredients used, which are country‐specific, as well as how they are cooked and/or prepared . Street food also raises some concerns regarding its safety, mostly because it is often prepared and sold in precarious conditions that lack sanitary surveillance and legal control .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of nutrient contributions from street foods, the highest contributions of street foods to daily energy intakes in adults were found in Abeokuta in Nigeria (50?3 %EI in males; 48?3 %EI in females) (13) , Ougadougou in Burkino Faso (46 %EI) (26) , Nairobi in Kenya (27-36 %EI in males; 13-22 %EI in females) (22) , Uganda (22?4-25?6 % EI) (29) and Bamako in Mali (18?3 %EI) (15)(16)(17) . In children, numerous studies including those in Cotonou in Benin (40 %EI) (3) , Nairobi in Kenya (13?4-22?4 %EI) (22) , Port-au-Prince in Haiti (25 %EI) (10) , Bamako in Mali (18?3 %EI) (15)(16)(17) , Hyderabad in India (19 %E) (11) and rural areas of Kenya (13)(14)(15)(16)(17)(18)(19)(20) (25) have demonstrated the contribution of street foods to daily energy intake.…”
Section: Energy and Nutrient Intakesmentioning
confidence: 99%
“…The street food sector in Sub-Saharan Africa is a source of affordable and nutritious meals for the urban poor (Lues, Rasephei, Venter, & Theron, 2006;Namugumya & Muyanja, 2012;Ohiokpehai, 2003;Steyn et al, 2014), while also being an important source of income for the women who dominate this sector Graffham, Zulu, & Chibanda, 2005;Nackerdien & Yu, 2017). In this study of the street food sector in Rwanda, Senegal and South Africa, micro-and informal enterprises are typically located in informal and formal trading areas along the streets and sidewalks near busy transport nodes and marketplaces.…”
Section: Introductionmentioning
confidence: 99%